Chronic Heart Disease and Comorbidity - Halimovich, Mavlonov Namoz (American Journal of Bioscience and Clinical Integrity, 2024)
Accompanying pathology aggravates course and prognosis of diseases. We examined in+ uence of comorbidity on unstable angina pectoris clinical course. / e course of angina pectoris has been estimated by Sietle Questionnaire of Stenocardia, comorbidity was estimated on Charlson comorbidity index. / Ere have been conducted electrocardiography, echocardiography, Holter monitoring, biochemical blood tests, glomerular 0 ltration rate MDRD, anthropometric data. 64 hospital patients with unstable angina pectoris were examined. / ere were detected a lot of associated diseases (from 2 to 6 in one patient), all the patients had chronic kidney disease. It has been revealed that increase in comorbidity is associated with increase of frequency of stenocardia, physical load limitation and quality of life impairment.